(untitled) (Intercom - Brazilian Journal of Communication Sciences, 2024)
This article goals to point out contributions of critical discourse studies for the analysis of products from the journalistic field from the study of climate change coverage. We take as an object an alternative media, Conexão Planeta, which maintains an engaged and contesting stance in the face of environmental injustices. The observation of the dichotomy North /South, articulated to the climate crisis, is privileged here, in order to study how the representations of its causes and solutions are amplified or silenced, even by vehicles that are not dominant and, theoretically, would have greater editorial freedom. to discuss the status quo. Among the results, we point out that the perspective of the South manifests itself in a limited way, with the predominance of alternatives to the crisis arising from hegemonic thinking, as well as the actors that usually appear in the traditional press.